1999
DOI: 10.1076/apab.107.2.84.4349
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of [3H]Glycine by Synaptosomes of Channel

Abstract: It is known that channel catfish erythrocytes can take up glycine by several distinct transport systems. Further, glycine is an inhibitory neurotransmitter in mammalian brain and spinal cord. Consequently, the uptake of [(3)H]glycine by catfish brain was investigated and found to be a saturable process, dependent on the presence of Na(++) and Cl(--) and sensitive to temperature. A kinetic analysis of transport was performed at 22C. This showed that a high-affinity system existed which exhibited a K(m) of 5.1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…These proteins belong to a family of Na + -coupled carriers that possess 12 hydrophobic plasma membrane-spanning regions [16]. We have previously reported that channel catfish brain has the ability to transport glycine by a system that can be stimulated by both Na + and Cl - [10]. That system had a K t of 5.1 ÌM, a similar value to the K d we now report.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…These proteins belong to a family of Na + -coupled carriers that possess 12 hydrophobic plasma membrane-spanning regions [16]. We have previously reported that channel catfish brain has the ability to transport glycine by a system that can be stimulated by both Na + and Cl - [10]. That system had a K t of 5.1 ÌM, a similar value to the K d we now report.…”
Section: Discussionsupporting
confidence: 71%
“…The energy for this active transport system is derived from the Na + gradient across the plasma membrane produced by the action of the sodium pump [12]. In the present study, we have measured the binding of [ 3 H]glycine to particles prepared from channel catfish brain and concluded that our observations represent binding to the transporters that previously we have shown to be responsible for [ 3 H]glycine uptake into synapsomes from these fish [10].…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…This uptake of glycine required Na + ions and bore the hallmark of a secondary active process reminiscent of system Gly. A similar glycine transport system has been examined in the brain of channel catfish [1,82]. Just over a decade ago, Ló pez-Corcuera et al [52] purified a glycine transporter from pig brainstem with a molecular weight of 100 kD.…”
Section: Glyt Transport Systemmentioning
confidence: 99%